KEPUASAN WISATAWAN TERHADAP WISATA VIRTUAL DI DKI JAKARTA - Muhammad Ali Fiqhie; Rudhi Achmadi (LPPM and Travel Operation Department Universitas Asa Indonesia, 2020)
This study aims to analyze tourist satisfaction with virtual tourism in DKI Jakarta. During the Covid-19 pandemic, all tourist attractions in DKI Jakarta were closed due to government provisions for large-scale social restrictions. Therefore, there are many tourists who cannot visit many tourist attractions and until finally some tour organizers create virtual tourism, which is a new form of travel during the pandemic. This research is important to find out how much satisfaction of tourists using virtual tourism in DKI Jakarta. The research was carried out from May to July 2020 in DKI Jakarta. This study was designed using a descriptive method. The sampling method used was accidental sampling method. This study uses the method of distributing questionnaires to obtain data and the method used is to distribute questionnaires to tourists who have used or participated in virtual tours using google form. By using several indicators to measure tourist satisfaction where the results of these indicators are the answers to the satisfaction received by tourists. The results of this study shows that the level of tourist satisfaction is around 3.89%. From these results, tourists are